Pengaruh Struktur Kepemilikan, Struktur Modal, GCG dan Ukuran Perusahaan Terhadap Kinerja Keuangan di BEI - Oktaviani Sinaga, Putri; Butarbutar, Hotlan; Melianna, Saur (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the influence of Ownership Structure, Capital Structure, Good Corporate Governance and Company Size on Company Financial Performance in Energy Sector companies listed on the Indonesia stock exchange for the period 2019-2023. The variables used in this study, the independent variable (X) consists of Ownership Structure proxied by Institutional Ownership (KI), Capital Structure proxied by Debt to Equity Ratio (DER), Good Corporate Governance proxied by Independent Board of Commisioners (DKI) and Company Size by Ln (TA) and the dependent variable (Y) is Financial Permormance proxied by Return on Assets (ROA). The sample in this study was obtained using the purposive side method.Based on the criteria and data processing process that were set, 25 companies were determined as research samples. The data analysis technique used was multiple linear regression. The results of this study state that the influence between ownership structuree, capital structutre, good corporate governance, and company size has a simultaneous effect on the financial performance of the Energy sector listed on the Indonesia Stock Exchange (IDX).